(untitled) (Physical Education, Health and Social Sciences, 2025)
This research investigates the integration of financial technology (Fintech) into Islamic banking, particularly focusing on its role in the assessment of Total Risk-Weighted Assets (TRWA). In the evolving digital economy, Islamic banks face distinctive challenges in managing risks due to their adherence to Shariah principles, which preclude interest-based transactions and speculative investments. These unique constraints necessitate novel risk evaluation frameworks. This study explores how Fintech innovations—such as artificial intelligence (AI), blockchain, big data analytics, and regulatory technology (RegTech)—can improve the transparency, accuracy, and efficiency of TRWA assessment within Islamic banking institutions. A mixed-methods approach was employed, incorporating both quantitative analysis of financial ratios (ROA, ROE, CAR) and qualitative insights from interviews with risk managers, executives, IT professionals, and Shariah scholars. The findings indicate that Fintech innovations significantly enhance the efficiency of risk management and the reliability of TRWA calculations. Moreover, Shariah compliance plays a moderating role, ensuring that technological solutions align with Islamic ethical standards. The study emphasizes the need for adaptive regulatory frameworks and collaborative development of Shariah-compliant Fintech solutions to support innovation without compromising core Islamic values. This research contributes to the literature on Islamic finance and Fintech by proposing a conceptual model that integrates technological advancements with ethical finance, offering practical implications for regulators, banks, and technology developers.